Theater Workshop: A Means to Promoting Crítical, Humanist and Creative Thinking Among Students. - Blanco Umaña, Juan Manuel (2022)
Since 2019 at the Universidad Nacional, Campus Sarapiquí, a theater workshop has been offered to the student community. This investigation sought to identity how in the student body this extracurricular activity complements their academic process of profesional studies, by analyzing the critical and humanistic thinking that characterize the creation processes in the group. Therefore, at the beginning, references that recognize the contributions of theater as a means for the dialogue of knowledge that foster skills or characteristics necessary for the development of humanistic, critical and therefore creative thinking were consulted. With the information collected, a self-administered questionnaire composed of open in addition to closed questions was developed, and applied to eleven paticipating students in the project, who have gone through the stages of choosing the theme, research, creation of the play and presentation to the public, which are necessary for the theatrical production and socialization of the collective reflection of the workshop. The data analysis allowed the investigation to identity that the majority of the students get the skills and abilities necessary for the development of critical and humanistic thinking. In addition, kwoledge transcends the artistic activity, complementing other learning processes and social relationships in which they interact. However, it is necessary to recognize the intentions of a theater workshop in a academic institution, to structure the methodology and mediation that allows the students to take advantage of the benefits of extracurricular activity.